Middle class in the Republic of Tatarstan: Analysis of the results of sociological research - Khayrullina, Yulduz R. (2018)
The article presents the results of the authors’ sociological study of the middle class, conducted in the Republic of Tatarstan. Based on the data obtained, the authors define its general stratification characteristics, and regional specific features of employment behaviour, consumer practices, life values and attitudes.